(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
ABSTRACT. This article examines the principal differences between General English and English for Specific Purposes in modern language teaching. General English is traditionally designed to develop broad communicative competence and overall language proficiency through grammar, vocabulary, speaking, listening, reading, and writing activities applicable to everyday communication. English for Specific Purposes, by contrast, is structured according to clearly defined academic, occupational, or professional needs and therefore focuses on target-oriented language use within specific discourse communities. The study analyzes differences in instructional objectives, curriculum design, lexical selection, methodological principles, teaching materials, teacher competence, and assessment systems. Particular attention is given to the growing role of ESP in higher education where students increasingly require language skills directly connected with future professional activities. Comparative analysis demonstrates that General English provides a linguistic foundation, whereas ESP increases practical relevance and learner motivation by directly linking language instruction with specialized communicative tasks. The findings suggest that effective differentiation between these two instructional models requires systematic needs analysis, authentic professional materials, and flexible curriculum design adapted to specific learner profiles.